Recognition of Engine Parameters for Mahua Biodiesel by Analyzing the Performance Using OFAT Approach - Sunil Dhingra (International Journal of Environmental Noise and Pollution Control, 2023)
The review work deals with the prediction of significant engine input parameters by the use of one factor at a time approach. The technique is a trial of experiments by varying only one engine input parameter and others remain at constant values. The various engine input parameters are found from the literature review. In the current work, six engine input parameters are predicted from the past research. These are blending ratio of biodiesel to diesel, compression ratio, load torque, engine speed in rpm, injection pressure and injection timing. It has been observed from OFAT approach that three significant engine parameters are Blending ratio, Compression ratio and load torque. These parameters are further used in optimizing the engine parameters for desirable performance, combustion and emission analysis. The design engineer can select any of the optimum combination of parameters depending upon the requirements.
Keywords: Engine parameters; Mahua biodiesel; OFAT approach; Performance; blending ratio; combustion; emission analysis